1979
DOI: 10.1016/0018-506x(79)90016-3
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin levels in peripheral blood and in cerebrospinal fluid during passive and active avoidance behavior in rats

Abstract: Vasopressin (AVP) levels were measured in plasma and cerebrospinal fluid (CSF) of rats during acquisition and retention of a passive avoidance response. Only 5 min after the onset of the retention session a significantly higher level of AVP was found in plasma of animals which displayed a long latency, as compared with the levels of animals which showed a weak passive avoidance response (short latencies), or no passive avoidance behavior at all (controls). Moreover no changes in plasma AVP levels were found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1

Year Published

1981
1981
1990
1990

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 24 publications
1
1
1
Order By: Relevance
“…Previous findings presented by Van Wimersma Greidanus et al (1979b) also support this hypothesis, although in that study CSF was withdrawn from the lateral ventricle and not from the cisterna magna as in the present experiments. This difference in CSF origin may account for the lower levels of AVP in CSF observed in the present experiment as compared to the previous study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous findings presented by Van Wimersma Greidanus et al (1979b) also support this hypothesis, although in that study CSF was withdrawn from the lateral ventricle and not from the cisterna magna as in the present experiments. This difference in CSF origin may account for the lower levels of AVP in CSF observed in the present experiment as compared to the previous study.…”
Section: Discussionsupporting
confidence: 84%
“…Thompson and De Wied (1973) have reported that the antidiuretic activity of eyeplexus blood in rats increased during a 24-hr postshock retention trial of a passive avoidance response. However, using a RIA, changes in AVP levels in peripheral blood and in ventricular CSF could not be demonstrated using various shock intensities during the learning trial, although these different shock intensities resulted in marked differences in avoidance latencies during retention (Van Wimersma Greidanus et al, 1979b). In the present study only one shock level was used during the learning trial and this induced a wide range of avoidance latencies during retention, which were not correlated to vasopressin levels in blood and CSF.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation